Rooting of coffee cuttings cv. ’mundo novo’ subjected to auxins and boron treatments - Ono, Elizabeth Orika; Rodrigues, João Domingos; de Pinho, Sheila Zambello; Rodrigues, Selma Szimidas (Pesquisa Agropecuaria Brasileira, 1993)
The present research aimed at studying the auxins and/or boron effect on rooting of coffee (Coffea arabica L. cv. ’Mundo Novo’) cuttings. The cuttings were obtained from semi-hardwood orthotropous branches of coffee-tree, containing two nodes and with approximately 10 cm length. The bases were dipped in treatment solutions composed of IBA or NAA with and without boron during 24 hours. After the treatments, the cuttings were planted in vermiculite. The following could be observed on cuttings taken 90 days after planting - total number of roots formed, average number of roots per cutting and root length. From the results obtained, it can be concluded that cutting treatment with NAA 100 ppm plus boron is responsible for the better rooting of coffee cuttings.